PUBLIC SERVICES BY THE VILLAGE GOVERNMENT IN KALIJATI VILLAGE SIDAMULIH DISTRICT PANGANDARAN REGENCY - Panji Mulya Rukmana; Kiki Endah; Ii Sujai (JGSRD: Journal of Government Science and Rural Development, 2023)
This research is based on the results of observations that the Public Service by the Village Government in Kalijati Village, Sidamulih District, Pangandaran Regency is still not optimal. The research method used is descriptive qualitative method. The types of data used are primary data, data collected by field researchers from the first source or the place where the research object is carried out and secondary data, namely report data; or official documents from the Kalijati Village Government, Sidamulih District, Pangandaran Regency. Data collection techniques used are observation, interviews, literature study and documentation. There were 8 informants in this study. Based on the results of the study, it is known that 1) Public Services by the Village Government in Kalijati Village, Sidamulih District, Pangandaran Regency are generally not optimal in their services according to Fandy Tjiptono's theory (1997:14). However, the Kalijati Village Government has done good services and is trying to improve its performance by utilizing existing facilities. In the Public Service there are several obstacles, namely the Village Government in Kalijati Village, Sidamulih District, Pangandaran Regency, among others, the Village Government in providing services to the community has not been maximized, there is no equipment complete, then there is no sense of understanding the needs of the community, in providing information the staff is still not optimal, and the ethics of the village staff are still not good in that the community is comfortable in communicating.